An Introduction to Collective Ijtihad: Concept and Application - Hasan, Aznan (Association of Muslim Social Scientists, 2003)
This Article explore the concept of collective ijtihad as a means of determining new judicial judgements.Accordingly, it analyzes the theoretical framework of this kind of ijtihad and its application by discussing the various institutions that practice it. In general, this article seeks to present this as a practical mechanism for ascertaining the Shari'ah's opinion concerning the Muslim ummah on a variety of current issues. At the outset, it will present briefly the controversy concerning the closure of the gate of ijtihad, for this kind of ijtihad relies heavily upon our recognition that, throughout the history of Islamic law, jurists have never abandoned the task of ijtihad